Pengelolaan Dana Desa Dalam Meningkatkan Kesejahteraan Masyarakat - Beatrice Nathania; Eko Deswin Miechaels Siringo-Ringo (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
In general, welfare means the fulfillment of all forms of life's needs, especially the basic ones such as food, clothing, housing, education, health care. Likewise, the National Family Planning Coordinating Board states that prosperity is a condition or condition of living that meets the requirements of a decent life, namely the fulfillment of basic needs, namely clothing, food, shelter, eating 3 times a day, and having different clothes, such as clothes for work, travel clothes, and everyday clothes at home. As it is also known that Human Resources in the village are still classified as having low creativity and participation in all activities in the village government, this is something that is interesting for the author how the village government and village communities must be able to manage Village Funds according to their needs. The community is required to be an actor in the management of the Village Fund, besides that the community and village government must also be active and carry out their respective functions. This is the background of the author to research on the management of the Village Fund in improving the welfare of the community. The results of this study are that the management of the Village Fund in Pamatang Sahkuda Village is running well so that the results of the management of the Village Fund are also in accordance with the needs of the community and are effective for the community. This success cannot be denied because of community participation in the management of the Village Fund, both in planning the priority use of the Village Fund, implementing the Village Fund or supervising project work and the results of the Village Fund project.